Polityka i teoria aktywizacji regionów w Polsce - Winiarski, Bolesław (Wydział Prawa i Administracji UAM, 1979)
The article contains a set of reflections concerning policy of activation of regions in Poland. The author endeavours to prove that undertakings connected with aecelaretion of economic development and with improvement of the state of their economies have had as a rule a compact character with main directions of the socio-economic policy of the state. Starting from the year 1918 the author has investigated actions connected with activation of regions development. The first step in that sphere was levelling regional disproportions after the period of the partitions of Poland. After the Second World War a fundamental problem of the state economic policy consisted in ensuring quick reconstruction processes, and — in spatial dimension — in ensuring integration of the coutry's economy within its new borders. That task was simultaneously a great activation operation. A great role had been played in searching for theoretical concepts by the research of the Poznań school under direction of S. Kruszczyński. An important role in research on methods of economic activation had also been played by Kraków and Warsaw centres. Actions of all centres have been co-ordinated by the National Commission of Spatial Development of the Polish Academy of Sciences with St. Leszczycki. International co-operation between the CMEA countries also contributed to activation processes of particular regions. The author states in the conclusion that activation operations were effective if they were connected with main directions of a development strategy determined by socio-economic policy on the national scale. From the scientific point of view the reserve (resource) theory of backward regions activation proved realistic and adequate, ithoogh especially strong for regions possessing raw materiails.
Policy and Theory of Regions Activation in Poland